Adherence and acceptance of a new oral nutritional supplement in cancer patients - a pilot study in crossover design - Hardt, Luisa; Konturek, Peter; Herrmann, Hans Joachim; Reljic, Dejan; Kugler, L.; Meyer, J.; Neurath, Markus; Zopf, Yurdagül (Journal of Physiology and Pharmacology, 2024)
Oral nutritional supplements (ONS) play a key role in the therapy of cancer-cachexia, but adherence to ONS-intake remains challenging. To improve adherence, a wide variety of ONS is crucial. We compared the acceptance and adherence of a commercial liquid ONS (LS) with a newly developed, energy- and protein-rich, semisolid, fruit-gum based product (FG) in oncological patients. Forty cancer patients with indication for artificial nutritional therapy were randomly assigned to LS and FG in crossover design for 4 weeks with a 1-week washout phase in-between. Adherence to ONS was recorded with MARS-D questionnaire. Sensory properties were evaluated and safety monitoring was performed. Energy and nutrient intake, nutrition and performance status and quality of life remained stable in both groups throughout the study (all p-values for the comparison between baseline and after 9 weeks were >0.05). Taste (p=0.004), smell (p=0.025) and enjoyment (p=0.027) of the LS were rated significantly better compared to FG and a higher adherence (p=0.005) for the LS was found. Nevertheless, patients were very interested about the new alternative of ONS, so that 16 of the study participants would buy it or strive for a medical prescription. The balanced, protein-rich ONS based on fruit gum is an innovative formulation that stabilizes nutritional status and might therefore extend the options for nutritional support in cancer patients in the future. However, the sensory properties must first be further improved to increase acceptance and adherence.
CRIS-Team Scopus Importer:2024-10-25
Keywords: cancer; oral nutritional supplement; cachexia; malnutrition; adherence; daily energy intake; body composition parameters; quality of life; sensory properties and preferences